Predicting a Sharp Decline in Selectivity for Catalytic Esterification of Alcohols from van der Waals Interactions. Issue 27 (28th April 2020) - Reece, Christian; Luneau, Mathilde; Friend, Cynthia M.; Madix, Robert J.
Abstract: Controlling the selectivity of catalytic reactions is a critical aspect of improving energy efficiency in the chemical industry; thus, predictive models are of key importance. Herein the performance of a heterogeneous, nanoporous Au catalyst is predicted for the complex catalytic self‐coupling of the series of C2 –C4 alkyl alcohols, based solely on the known kinetics of the elementary steps of the catalytic cycle for methanol coupling, using scaling methods augmented by density functional theory. Notably, a sharp decrease in selectivity for ester formation with increasing molecular weight to favor the aldehyde due to van der Waals interactions of reaction intermediates with the surface was predicted and subsequently verified quantitatively by experiment. Further, the agreement between theory and experiment clearly demonstrates the efficacy of this approach for building a predictive model of catalytic behavior for a homologous set of reactants using a small set of experimental information. Abstract : More efficient kinetics : By combining experimentally measured kinetic parameters with density functional theory to compute van der Waals interactions, it is possible to efficiently scale a whole set of rate constants for the homologous set of alcohol self‐coupling reactions. The strong van der Waals interactions between the higher alcohol intermediates and the surface are found to drive the decrease in selectivity to coupling.